William H. Baily, The Revised Ordinances of Nineteen Hundred of the City of Des Moines, Iowa, at 89-90, (1900), Ordinances City of Des Moines, Weapons, Concealed, § 209 - (:unkn) unknown (General Publisher, 1900)
Prohibited the carrying of a concealed pistol or other firearms, slungshot, brass knuckles, or knuckles of lead, brass or other metal or material, or any sandbag, air guns of any description, dagger, Bowie knife, dirk knife, or other knife or instrument for cutting, stabbing or striking, or other dangerous or deadly weapon.
--
Keywords: CARRY - CONCEALED